Avian Gut Function in Health and Disease Poultry Science Symposium Series Volume Twenty-eight - Perry, G.C (CABI, 2014)
The proceedings which comprise this volume are taken from the 28th Symposium in a series organized by the UK branch of the World’s Poultry Science Association. The chosen topic attracted a large audience, members of which came from all continents except South America. This probably demonstrates the importance that poultry scientists and industries worldwide attach to avian gut function. Since the late 1960s, when the Swann Committee in the UK investigated the use of antibiotics in animal husbandry and veterinary medicine, pressure on their use as growth promoters has grown. Swann recommended that only antibiotics which ‘have little or no application as therapeutic agents in man or animals and will not impair the efficacy of a prescribed therapeutic drug or drugs through the development of resistant strains of organisms’ should be used for growth promotion. The UK government accepted these recommendations and, subsequently, the European Union adopted this principle, although it had to resist pressure from Sweden for a complete ban on antibiotic growth promoters.